Pelatihan Speech Berbasis Flipped Learning untuk Meningkatkan Kemampuan Speaking dan Kepercayaan Diri Siswa English Club SMPN 4 Kuningan dalam Program Talent Show - Nur Imani, Mutia; Mutmainah, Nisaul; Fitri, Nurul Khurmatil; Nugroho, Muhammad Aprianto Budie (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2025)
The Speech training and Talent Show program were forms of community service conducted at SMP Negeri 4 Kuningan, targeting members of the English Club as participants. This program aimed to improve students' English-speaking skills through the Flipped Learning (Flipped Classroom) approach, which integrated online training via WhatsApp with offline (in-person) sessions. The training focused on enhancing the speaking skills and self-confidence of English Club members through speech performance. The culmination of the activity was marked by a Talent Show featuring student speeches on the theme of “Bullying and Friendship”, delivered in front of the entire school community. Based on evaluations conducted through direct observation and student questionnaires, the program demonstrated significant improvements in students’ self-confidence, pronunciation, and their ability to deliver speeches effectively.